RESEARCH TRENDS IN SCIENCE PROCESS SKILLS IN EDUCATION: BIBLIOMETRIC ANALYSIS OF SCOPUS PUBLICATIONS 2019-2024 - Muhammad Iqbal; Edi Istiyono; Siti Nurjanah; Moh. Slamet Sutrimo; Muh. Ikhwan Fauzan (EduFisika: Jurnal Pendidikan Fisika, 2025)
Research related to Science process skills has been carried out for a long time. To find out trends related to the development of science process skills research, research was carried out related to this topic. This research is a literature review research with bibliometric analysis carried out on science process skills articles published in Scopus indexed journals from 2019- 2024. The literature review was obtained through the help of Publish or Perish with a total of 297 articles obtained and selection was carried out using the PRISMA method so that 134 articles were analyzed. The analysis was carried out with the help of Excel and VOSViewer. The results of the analysis show how publisher, author, country, affiliation and keywords are most related to the topic of science process skills. Research shows that there is a positive trend in the number of publications related to the topic of science process skills and the results show that countries in Asia and Africa have done the most research on this topic. Indonesia is the country that publishes the most on this topic and its articles are the most cited with 502 citations. The results also show that science process skills are currently very closely related to the inquiry model, STEAM, critical thinking and creative thinking.